Religious Policies and Scientific - Educational Status of Syria –since the Time of Atabakan e- Zangi till the end of Mamluks Era- - Hossein Izadi; Shahnaz Karimzadeh Sureshjani (تاریخ اسلام)
Since the earliest Islamic centuries the development of Shiite trends has been constantly one of the concerns of governments in the strategic areas of Syria including the present district of Syria, Lebanon, Palestine, and Jordan. The rulers of this area, since the time of Atabakan e- Zangi -521-624 After Hijrah- till the end of Mamluks era -650-922 After Hijrah- followed their policy to strengthen the traditions of Sunnites through the development of schools. This issue led to the development of narrative sciences and prevalence of selfism due to their adequate dynamism. At this time, Shiite could provide the ground toward the improvement of Shiite beliefs and their propagation in the other areas. This writing is to study the religious policies as well as the educational-scientific status of Syria in this span of time through the investigation of primary historical sources.